Understanding the extensive hybridization in South American Nothofagus through karyotype analysis - Acosta, María Cristina; Premoli Il'grande, Andrea Cecilia (Botanical Journal of the Linnean Society)
Extensive phylogeographic and population studies in Nothofagus revealed that hybridization, introgression and plastid capture are common phenomena that have occurred throughout the evolutionary history of the genus. Here, detailed karyotypes of ten South American Nothofagus spp. were constructed using chromosome fluorescent banding with the aim of (1) investigating if karyotype features were compatible with the formation of fertile interspecific hybrids, particularly when growing in sympatry and (2) identifying species-specific chromosomal markers to enable further studies of hybridization in Nothofagus. Similar karyotype formulas and heterochromatin patterns among species of the same clade (i.e. subgenus) revealed a low rate of chromosomal change. This finding reinforces the idea that hybrids between Nothofagus spp. can be fertile and that chromosome pairing in meioses could be successful. Genome conservation and extensive hybridization that resulted in plastid capture has been observed in other woody genera. Hybridization in tree species could be a survival strategy to enable the successful colonization of sites after disturbance and the introgression of genes from their congeners (adaptive introgression) may play an important role in adapting to climate change. Finally, N. antarctica has one more nucleolus organizing region (NOR) than its congeners that is easily identifiable and therefore could be used in future studies of hybrids. Fil: Acosta, María Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Premoli Il'grande, Andrea Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del ...